Small molecule inhibition of IRE1α kinase/RNase has anti-fibrotic effects in the lung - Thamsen, Maike (PLoS One, 2019)
Endoplasmic reticulum stress (ER stress) has been implicated in the pathogenesis of idiopathic pulmonary fibrosis (IPF), a disease of progressive fibrosis and respiratory failure. ER stress activates a signaling pathway called the unfolded protein response (UPR) that either restores homeostasis or promotes apoptosis. The bifunctional kinase/RNase IRE1α is a UPR sensor/effector that promotes apoptosis if ER stress remains high and irremediable (i.e., a “terminal” UPR). Using multiple small molecule inhibitors against IRE1α, we show that ER stress-induced apoptosis of murine alveolar epithelial cells can be mitigated in vitro. In vivo, we show that bleomycin exposure to murine lungs causes early ER stress to activate IRE1α and the terminal UPR prior to development of pulmonary fibrosis. Small-molecule IRE1α kinase-inhibiting RNase attenuators (KIRAs) that we developed were used to evaluate the contribution of IRE1α activation to bleomycin-induced pulmonary fibrosis. One such KIRA—KIRA7—provided systemically to mice at the time of bleomycin exposure decreases terminal UPR signaling and prevents lung fibrosis. Administration of KIRA7 14 days after bleomycin exposure even promoted the reversal of established fibrosis. Finally, we show that KIRA8, a nanomolar-potent, monoselective KIRA compound derived from a completely different scaffold than KIRA7, likewise promoted reversal of established fibrosis. These results demonstrate that IRE1α may be a promising target in pulmonary fibrosis and that kinase inhibitors of IRE1α may eventually be developed into efficacious anti-fibrotic drugs.